2021
DOI: 10.3390/agriculture11010024
|View full text |Cite
|
Sign up to set email alerts
|

Possibly Invasive New Bioenergy Crop Silphium perfoliatum: Growth and Reproduction Are Promoted in Moist Soil

Abstract: The cup plant (Silphium perfoliatum) is a new and promising bioenergy crop in Central Europe. Native to North America, its cultivation in Europe has increased in recent years. Cup plant is said to be highly productive, reproductive, and strongly competitive, which could encourage invasiveness. Spontaneous spread has already been documented. Knowledge about habitat requirements is low but necessary, in order to predict sites where it could spontaneously colonize. The present experimental study investigates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
5
13
0
Order By: Relevance
“…Our results are in line with studies (Ende et al 2021;Schoo et al 2017a) that have refuted the initial assumption that the cup plant suits very well for cultivation under drier soil conditions (Bauböck et al 2014;Pan et al 2011;Sokolov and Gritsak 1972). Although Schoo et al (2017b) have shown that cup plant has not a higher water capture capacity than maize, the enduring rooting system in the subsoil may be favorable.…”
Section: More Intense Rooting Of Deeper Soil Layers By Cup Plantsupporting
confidence: 92%
“…Our results are in line with studies (Ende et al 2021;Schoo et al 2017a) that have refuted the initial assumption that the cup plant suits very well for cultivation under drier soil conditions (Bauböck et al 2014;Pan et al 2011;Sokolov and Gritsak 1972). Although Schoo et al (2017b) have shown that cup plant has not a higher water capture capacity than maize, the enduring rooting system in the subsoil may be favorable.…”
Section: More Intense Rooting Of Deeper Soil Layers By Cup Plantsupporting
confidence: 92%
“…This was possibly because all the investigated sites had an average EIV soil moisture. But the preference of cup plants for moist sites was also confirmed by experimental studies in Germany by Ende et al (2021), where it showed higher biomass and reproductive potential under moist soil conditions. Therefore, special attention must be paid to moist habitats because they are often valuable for nature conservation and could be colonized by the cup plant (Ende et al 2021).…”
Section: Discussionmentioning
confidence: 65%
“…In fact, losing of crop and thus of fruits from the trailer is quite possible and must be kept in mind regarding the prevention of cup plant spread. A dispersal of the fruits and of root parts via water would also be conceivable and was suspected by Ende et al (2021) and Vladimirov (2021). Altogether, we suspect a certain dispersal potential of cup plant -even over longer distances.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported to have a dry matter yield per hectare that is about 20% lower, and a methane yield that is about 35% lower than that of silage maize (Gansberger et al, 2015). On soils with a high water supply, the cup plant has the potential to achieve higher biomass yields than usual (Ende et al, 2021; Schoo, Schroetter, et al, 2017), but methane yields are still generally lower than in silage maize (Ruf & Emmerling, 2022). Cup plant was found to improve the soil fertility and its greenhouse gas balance due to carbon sequestration and enhanced soil formation (Feldwisch, 2011; Franzaring et al, 2015).…”
Section: Introductionmentioning
confidence: 99%